Development of an alternating tangential flow (ATF) perfusion‐based transient gene expression (TGE) bioprocess for universal influenza vaccine. (29th May 2019) - Hong, Jinsung; Demirji, Jacob; Blackstock, Daniel; Lee, James; Dinh, Tracey; Goh, Alvenne; Arnold, Frank; Horwitz, Joe
Abstract: An alternating tangential flow (ATF) perfusion‐based transient gene expression (TGE) bioprocess has been developed using human embryonic kidney (HEK) 293 cells to produce H1‐ss‐np, a promising candidate for a universal influenza vaccine. Two major adjustments were taken to improve the process: (1) eliminate the interference of microbubbles during gene transfection; and (2) utilize an ATF perfusion system for a prolonged culture period. As a result, a closed‐operation 9‐days ATF perfusion‐based TGE bioprocess was developed. The TGE bioprocess showed continuous cell growth with high cell viability and prolonged cellular productivity that achieved recombinant product level of ~270 mg/L which was more than two times that of 4‐days base‐line TGE bioprocess. In addition, the consumables cost per milligram for ATF perfusion‐based TGE bioprocess was ~70% lower than that of the base‐line TGE bioprocess suggesting high cost savings potential in vaccine manufacturing. Based on the lower contamination risk, higher productivity, and cost efficiency, the ATF perfusion‐based TGE bioprocess can likely provide potential benefits to many future applications in vaccine and drug manufacturing.